FLOODLOG as the project on the use of GIS in the security practice and flood crisis management education - KELEMEN, Miroslav; BLIŠŤANOVÁ, Monika (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2014)
The aim of this paper is the idea of using ArcGIS systems at the platform of results within the international cross-border project HUSK: Flood modelling and logistic model development for flood crisis management, as the tool in the security practice and crisis management education. Planning is an important element in each process separately and is particularly important in protecting the health and property of the population. but also rescuers. Contribution emphasizes the importance of input data for each phase of crisis management and the protection of rescuers too.